Supporting the active learning of collaborative database browsing techniques - P. Sawyer; T. Rodden; J. A. Mariani; M. B. Twidale; D. M. Nichols (Association for Learning Technology, 1995)
The proliferation of databases has led to a growing demand for skills in navigating and manipulating them. These skills are important not just in order to undertake study and research in Higher Education, but as an important transferable skill likely to be expected by industry and commerce of all graduates. We are developing a system that can more effectively support the browsing of library databases. In particular we are interested in developing an interface to support the process of collaborative browsing.